Fuel Production From Non-Food Biomass 2015
DOI: 10.1201/b18437-9
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Corn Stover Pretreated with Liquid Hot Water and Fed-Batch Semi-Simultaneous Saccharifi cation and Fermentation for Bioethanol Production

Abstract: Background: Previous research on alkaline pretreatment has mainly focused on optimization of the process parameters to improve substrate digestibility. To achieve satisfactory sugar yield, extremely high chemical loading and enzyme dosages were typically used. Relatively little attention has been paid to reduction of chemical consumption and process waste management, which has proven to be an indispensable component of the biorefineries. To indicate alkali strength, both alkali concentration in pretreatment so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 15 publications
(14 reference statements)
3
37
1
1
Order By: Relevance
“…hemicellulose, cellulose and lignin), the cellulosic fraction was not significantly affected by pre-treatment with alkali, whereas hemicellulose was significantly solubilized. In a recent study, where corn stover was pretreated with NaOH to increase its enzymatic hydrolysis, more than 95% of the cellulosic fraction was preserved (Chen et al 2013); it was also shown that when NaOH loading increased from 0.04 to 0.1 g/g corn stover, degradation of hemicellulose (xylan) was increased by 20%. Rezende et al (2011) pre-treated SCB with various loadings of NaOH to enhance its enzymatic digestibility; in general, compositional analysis of SCB pre-treated by various loading of NaOH showed that alkaline pretreatment resulted in a significant increase in hemicellulose and lignin solubilization, whereas cellulosic fraction was well preserved and its concentration increased in retained solids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…hemicellulose, cellulose and lignin), the cellulosic fraction was not significantly affected by pre-treatment with alkali, whereas hemicellulose was significantly solubilized. In a recent study, where corn stover was pretreated with NaOH to increase its enzymatic hydrolysis, more than 95% of the cellulosic fraction was preserved (Chen et al 2013); it was also shown that when NaOH loading increased from 0.04 to 0.1 g/g corn stover, degradation of hemicellulose (xylan) was increased by 20%. Rezende et al (2011) pre-treated SCB with various loadings of NaOH to enhance its enzymatic digestibility; in general, compositional analysis of SCB pre-treated by various loading of NaOH showed that alkaline pretreatment resulted in a significant increase in hemicellulose and lignin solubilization, whereas cellulosic fraction was well preserved and its concentration increased in retained solids.…”
Section: Discussionmentioning
confidence: 99%
“…Alkaline pre-treatment (using either lime or sodium hydroxide, or combination of them) for enhancing either ruminal digestibility or enzymatic digestibility in cellulosic-ethanol production process has been widely attempted (Haddad et al 1998;Xu & Cheng 2011;Ahmadi et al 2013;Chen et al 2013). For example, combination of sodium hydroxide and lime to enhance the enzymatic hydrolysis in lignocellulosic-ethanol production process was reported by Xu and Cheng (2011) in which, at the recommended conditions [6 h, 21°C, 1.0% (w/w) NaOH, and 0.2% (w/w) Ca(OH) 2 ], the glucose and xylose yields of switchgrass reached 59.4% and 57.3% of their theoretical yields, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Kang ve arkadaşları kolza atıkları ile yapmış oldukları çalışmada 55ºC gibi düşük sıcaklıklarda alkali derişiminin ve ön işlem süresinin etkisi olmadığını, ancak ön işlem süresinin yüksek alkali derişiminde etkili olduğunu ve düşük ön işlem süresinin enzimatik hidroliz üzerine etkin olmadığını bildirmişlerdir [33]. Alkali derişiminin lignin giderimi kadar hemiselüloz giderimi (çözünmesi/hidroliz olması) üzerine de etkili olduğu bilinmektedir [34]. Bu çalışmada, NaOH derişiminin %0,5 olduğu durumda çok düşük olan hemiselüloz gideriminin, alkali derişiminin %2,25'e yükseltilmesiyle anlamlı bir şekilde arttığı görülmektedir (Şekil 4).…”
Section: Naoh Derişiminin Fındık Kabuğunun Bileşimi Ve Enzimatik Hidrunclassified
“…We studied the effects of different pretreatment parameters, including alkali loading, temperature, and residence time, on the recovery and subsequent enzymatic digestion of PBD manure fiber ( Table 2). We used low-severity protocols to evaluate pretreatment under conditions that minimized the cost of chemicals and the energy needed to heat the samples: 100°C for 5 min at concentrations of 2 − 10% (by dry fiber weight) of NaOH and NH 3 [41,58]. These pretreatment protocols led to substantial decreases in fiber residual lignin (16 − 40% delignification) and improved carbohydrate recovery (80-67%) and higher carbohydrate concentration (2-10%).…”
Section: Alkaline Pretreatment Of Pbd Manure Fibermentioning
confidence: 99%
“…Alkaline biomass pretreatment methods using either sodium hydroxide [40,41] or aqueous ammonia [42] have been studied in recent years and shown to have high efficiency and low cost [14,38]. Sodium hydroxide treatment effectively depolymerizes and removes the most labile biomass components, such as hemicelluloses and lignin, causes swelling that increases enzyme accessible surface area (for solvation and saponification reactions) and reduces the degree of polymerization and crystallinity of cellulose [40]. Aqueous ammonia reacts selectively with lignin by cleaving C-O-C bonds in lignin and ether and ester bonds in lignincarbohydrate complexes, but carbohydrate removal and/ or degradation is limited.…”
Section: Introductionmentioning
confidence: 99%